Pseudospectra and eigenvalue asymptotics for disordered non-selfadjoint operators in the semiclassical limit - Vogel, Martin (Frontiers in Applied Mathematics and Statistics, 2024)
The purpose of this note is to review certain recent results concerning the pseudospectra and the eigenvalues asymptotics of non-selfadjoint semiclassical pseudo-differential operators subject to small random perturbations.